How COVID-19 and other pathological conditions and medical treatments activate our intravascular innate immune system - Nilsson, Bo; Eriksson, Oskar; Fromell, Karin; Persson, Barbro; Ekdahl, Kristina N. (Frontiers in Immunology, 2023)
COVID-19 has been shown to have a multifaceted impact on the immune system. In a recently published article in Front Immunol, we show that the intravascular innate immune system (IIIS) is strongly activated in severe COVID-19 with ARDS and appears to be one of the causes leading to severe COVID-19. In this article, we describe the IIIS and its physiological function, but also the strong pro-inflammatory effects that are observed in COVID-19 and in various other pathological conditions and treatments such as during ischemia reperfusion injury and in treatments where biomaterials come in direct contact with blood in, e.g., extracorporeal and intravasal treatments. In the present article, we describe how the IIIS, a complex network of plasma proteins and blood cells, constitute the acute innate immune response of the blood and discuss the effects that the IIIS induces in pathological disorders and treatments in modern medicine.